(untitled) (Research, Society and Development, 2022)
Disc problems should be treated with appliances or plates that are more efficient than others at returning the disc to its normal position in the mandibular fossa. It was noted that there is a lack of comparative studies showing which are the most efficient plates, which ends up generating a need for research to verify which are the most efficient plates in the treatment of signs and symptoms. Therefore, the present study aimed to verify different types of bite plate for the treatment of temporomandibular disorders (DTM). We sought to define the mechanisms that make the bite device work well in occlusal therapy and to detect the advantages of each bite plate device. In the methodology, a systematic review of the literature was carried out based on the periodic databases, Google Scholar and Scielo, whose time frame was between the years 2016 to 2021, which after being collected and analyzed, 16 remained for the discussion of this study. In the results, it became evident that the disorders of the Temporomandibular Joint (ATM) and muscles basically consist of the problems of the muscles and the articular disc. Therefore, just one type of bite plate may be sufficient to eliminate the signs and symptoms associated with the muscles and disc of the ATM.